THE EFFECT OF INVENTORY INTENSITY AND REAL EARNINGS MANAGEMENT ON TAX AVOIDANCE IN COMPANIES MINING SECTOR ON THE INDONESIA STOCK EXCHANGE 2020-2023 - Crismes Ulina Ritonga; Desy Astrid Anindya; Ikbar Pratama (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study was conducted to determine the effect of Inventory Intensity and Real Earnings Management on Tax Avoidance in Mining Sector Companies on the Indonesia Stock Exchange in 2020-2023. Based on the predetermined research hypothesis, it is known that inventory intensity and real earnings management have an effect on tax avoidance. The type of quantitative research with a causal associative approach. The population is 42 mining sector companies with a purposive sampling technique of 27 companies over a period of 5 years with a total of 108 data. The fund processing technique uses multiple linear regression analysis. The results of the study indicate that partially inventory intensity has a positive and significant effect on tax avoidance, but real earnings management does not affect tax avoidance. Simultaneously, inventory intensity and real earnings management have a significant effect on tax avoidance.